1986
DOI: 10.1073/pnas.83.17.6656
|View full text |Cite
|
Sign up to set email alerts
|

Multiple calcium channels mediate neurotransmitter release from peripheral neurons.

Abstract: We examined the effects of dihydropyridine drugs on evoked neurotransmitter release from cultured neonatal rat sensory and sympathetic neurons. Depolarization with K+-rich solutions increased the release of substance P from cultured sensory neurons. This release was enhanced by BAY K8644 and (+)-202791 and was blocked by a variety of other dihydropyridines including (-)-202791, by Co2+, or in Ca2+-free solutions. K+-rich solutions also stimulated the release of [3Hjnorepinephrine from cultured sympathetic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
3

Year Published

1987
1987
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(126 citation statements)
references
References 30 publications
7
116
3
Order By: Relevance
“…High-affinity binding of dihydropyridines to nervous tissue has been demonstrated, and it has been proposed that these binding sites are L-type calcium channels. 19 However, in functional studies in which an inhibition of evoked norepinephrine release was observed by dihydropyridines and verapamil, it only occurred either at high stimulation frequencies (Ն10 Hz) or at drug concentrations Ն1 mol/L. 19 -23 In the present study, even 1 mol/L verapamil failed to inhibit evoked norepinephrine release at stimulation frequencies of up to 10 Hz.…”
Section: Discussioncontrasting
confidence: 36%
“…High-affinity binding of dihydropyridines to nervous tissue has been demonstrated, and it has been proposed that these binding sites are L-type calcium channels. 19 However, in functional studies in which an inhibition of evoked norepinephrine release was observed by dihydropyridines and verapamil, it only occurred either at high stimulation frequencies (Ն10 Hz) or at drug concentrations Ն1 mol/L. 19 -23 In the present study, even 1 mol/L verapamil failed to inhibit evoked norepinephrine release at stimulation frequencies of up to 10 Hz.…”
Section: Discussioncontrasting
confidence: 36%
“…They are, however, consistent with previous studies on presynaptic nerve terminal Ca channels at many fast-transmitting synapses using more indirect techniques. These include insensitivity to DHP blockers (see Nachsen and Blaustein, 1979;Pemey et al, 1986;Miller, 1987;Himing et al, 1988;Suszkiw et al, 1989), slow inactivation (Suszkiw et al, 1986), and sensitivity to w-CTX (Kerr and Yoshikami, 1984;Yoshikami et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…It was initially proposed that either w-conotoxin (Miller, 1987) or dihydropyridine-sensitive HVA Zc, (Pemey et al, 1986;Rane et al, 1987) could mediate synaptic transmission. However, Regan et al (1991) have recently shown that in hippocampal cells, as in other mammalian neurons, much of the HVA IC, is resistent to both w-conotoxin and dihydropyridine blockers.…”
Section: Specificity Of H Va I Enhancementmentioning
confidence: 99%